2019
DOI: 10.1007/s00217-019-03311-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical parameters profile analysis by liquid chromatography and antioxidative activity of the Saskatoon berry fruits and their components

Abstract: The main goals of the study were to determine nutritional parameters including contents of organic acids, sugars, and bioactive compounds as well as the antioxidant activity of fruits and fruit components of seven selected Saskatoon berry (Alnifolia alnifolia) genotypes. Fruits of three Polish clones ('no 5/6', 'type N', and 'type S') and of four Canadian cultivars ('Martin', 'Pembina', 'Smoky', and 'Thiessen') and their components including peel, flesh and seeds were used in the study. The antioxidant potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…It was confirmed that the peel was red and contained about twice more anthocyanins compared to the flesh. According to literature, the value of a* parameter measured in the chokeberry fruit is similar, which is confirmed in the reports by Horszwald et al [28] and Lachowicz et al [29].…”
Section: Resultssupporting
confidence: 86%
“…It was confirmed that the peel was red and contained about twice more anthocyanins compared to the flesh. According to literature, the value of a* parameter measured in the chokeberry fruit is similar, which is confirmed in the reports by Horszwald et al [28] and Lachowicz et al [29].…”
Section: Resultssupporting
confidence: 86%
“…The caloric value of the fruit is averaged at 85 kcal/100 g [ 12 ]. The main groups of polyphenols found in the fruit of the Saskatoon berry include flavanols, anthocyanins, flavonols and phenolic acids [ 15 ]. The fruit peel of the Saskatoon berry is rich in anthocyanins, including cyanidin derivatives, flavonols and quercetin derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorogenic acid was not detected in mango fruit leather or reported in fresh mango pulp [40]. Quinic acid is also a major bioactive chemical found in Saskatoon berry genotypes [42]. Thus, the presence of these phenolic acids increases the potential of mango-Natal plum leather as a functional snack.…”
Section: Correlation Between the Predominant Cyanidin Components Of Cmentioning
confidence: 92%